Potter's Sequence - Shastry, Srikanth M. (Medknow Publications & Media Pvt Ltd, 2012)
Potter's sequence is a rare fatal disorder that occurs in sporadic and autosomal recessive forms with an incidence of 1 in 4000 births. Babies born with this condition are either still born or die very early within the neonatal period. We report a case of Potter's sequence with the typical physical findings and histological findings.